La política exterior del Gobierno Revolucionario Peruano y los cambios en el orden internacional, 1968-1975 - Alcalde Cardoza, Javier; Romero Sommer, Gonzalo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
The Peruvian military government followed between 1968 and 1975 a foreign policy aiming to connect the reforms it pursued internally with reforms proposed by the Group of 77 to the international economic order; it connected also its internal policies with a nationalist current in Latin America that was attempting to restructure the Inter-American System. In doing this, the Peruvian government transformed both the Paradigm and the Grand Strategy of Peruvian foreign policy and presented a challenge to the US hemispheric hegemony. The article explains internal and external conditions that made possible the changes in Peruvian foreign policy and briefly describes the regional and global development of this policy. It explains also how the evolution of some of the aforementioned conditions brought the decline of the revolutionary foreign policy from 1973.

El gobierno militar peruano desarrolló entre 1968 y 1975 una política exterior encaminada a vincular las reformas internas que perseguía con las reformas al orden económico internacional que planteaba el Grupo de los 77 así como con los intentos de reajustar el orden interamericano propugnados por una corriente nacionalista latinoamericana. Al hacer esto, transformó tanto el Paradigma como la Gran Estrategia de la política exterior peruana y configuró un desafío a la hegemonía hemisférica estadounidense. El artículo explica las condiciones internasy externas que propiciaron el cambio en las acciones de Lima y reseña someramente las dimensiones regional y global de estas. Explica también cómo la evolución de algunas de estas condiciones trajo el ocaso de la política exterior revolucionaria a partir de 1973.
Foreign policy of the Peruvian Revolutionary Government and Changes in the International Order, 1968-1975
Keywords: Perú; Gobierno militar 1968-1975; Política exterior; Estados Unidos; Grupo de los 77; Nuevo Orden Económico Internacional; Gran Estrategia; https://purl.org/pe-repo/ocde/ford#5.09.01